The effects of virtual logotherapy on health-promoting lifestyle among single-parent adolescent girls during the coronavirus disease 2019 pandemic: a randomized clinical trial - Fatemeh Hosseinzadeh; Reza Negarandeh; Akram Sadat Sadat-Hoseini; Shahzad Pashaeypoor (BMC, 2023)
Abstract Single-parent adolescents are vulnerable individuals and it is necessary to improve their health, particularly during epidemics. This study aimed to investigate the effects of virtual logotherapy (VL) on health-promoting lifestyle (HPL) among single-parent adolescent girls during the COVID-19 pandemic. This single-blind randomized clinical trial was conducted on 88 single-parent adolescent girls recruited from the support organization for vulnerable individuals in Tehran, Iran. They were randomly allocated to a control and an intervention group through block randomization. Participants in the intervention group received VL in three-five person groups in 90 min biweekly sessions. The Adolescent Health Promotion Short-Form was used to assess HPL. Data were analyzed using the SPSS software (v. 26.0) and through the independent-sample t, Chi-square, Fisher's exact, and Mann-Whitney U tests. There was no significant difference between the intervention and the control groups respecting the pretest mean score of HPL (73.58±16.74 vs. 72.80±9.30; P=0.085). However, the posttest mean score of HPL in the intervention group (82 with an interquartile range of 78-90) was significantly more than the control group (71.50 with an interquartile range of 63.25-84.50) (P=0.001). Moreover, after adjusting the effects of the significant between-group differences respecting pretest mean scores, the pretest-posttest differences of the mean scores of HPL and all its dimensions in the intervention group were significantly more than the control group (P<0.05). VL is effective in significantly improving HPL among single-parent adolescent girls. Healthcare authorities are recommended to use VL for health promotion among single-parent adolescents. Trial registration This research was registered (17/05/2020) in the www.thaiclinicaltrials.org with registration number: TCTR20200517001.